2013
DOI: 10.1111/aas.12104
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged inspiratory time produces better gas exchange in patients undergoing laparoscopic surgery: A randomised trial

Abstract: A prolonged inspiratory time demonstrated a beneficial effect on oxygenation. Furthermore, it showed better CO2 elimination without elevating the peak or plateau airway pressure compared with applying external PEEP. In terms of gas exchange and respiratory mechanics, a prolonged inspiratory time appears to be superior to applying external PEEP in patients undergoing laparoscopic surgery in the Trendelenburg position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 36 publications
1
52
0
1
Order By: Relevance
“…However, previous studies report that prolonged inspiratory time did not deteriorate but rather improved CO 2 removal by decreasing airway dead space and increasing alveolar ventilation [4,23,24]. In addition, pressure-controlled ventilations with I/E ratios of 1:1 and 1:2 showed comparable CO 2 removal during laparoscopic bariatric surgery [6].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, previous studies report that prolonged inspiratory time did not deteriorate but rather improved CO 2 removal by decreasing airway dead space and increasing alveolar ventilation [4,23,24]. In addition, pressure-controlled ventilations with I/E ratios of 1:1 and 1:2 showed comparable CO 2 removal during laparoscopic bariatric surgery [6].…”
Section: Discussionmentioning
confidence: 90%
“…Prolonged I/E ratio ventilation, for example 1:1 or 2:1, was used to improve arterial oxygenation in patients with lung injury [3]. Studies on prolonged I/E ratio ventilation during laparoscopic surgery and one lung ventilation also reported favorable results in terms of oxygenation and respiratory mechanics [4,5]. Recently, prolonged I/E ratio ventilation of 1:1 was reported to improve arterial oxygenation in morbidly obese patients undergoing bariatric surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pressurecontrolled ventilation was found to result in greater dynamic compliance and lower peak inspiratory airway pressure, compared with volume-controlled ventilation [30]. A prolonged inspiratory duration can be an alternative to producing better gaseous exchange conditions and respiratory mechanics [31]. I : E ratios of 2 : 1 or 1 : 1 provided better oxygenation and lower PaCO 2 levels than the conventional 1 : 2 ratio by preserved Vd/Vt in the steep Trendelenburg position.…”
Section: Prostatectomymentioning
confidence: 99%
“…A study demonstrated that the ventilation in VCV mode with an inspiratory/expiratory ratio (I:E) of 1:1 or 2:1 rises mean Paw and maintains oxygenation during pneumoperitoneum (65). A 5-cmH2O PEEP with I:E=1:2 produces the same outcomes, but increases peak and plateau pressures.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%